Implementation of DEIS for reliable fault monitoring and detection in PEMFC single cells and stacks. (1st December 2018) - Darowicki, K.; Janicka, E.; Mielniczek, M.; Zielinski, A.; Gawel, L.; Mitzel, J.; Hunger, J.
Abstract: Dynamic Electrochemical Impedance Spectroscopy (DEIS) was presented as novel method for diagnostic and monitoring of PEMFC stack and single cells operation. Impedance characteristics were obtained simultaneously with current - voltage characteristics for stack and each individual cell. Impedance measurements were performed in galvanodynamic mode. It allowed to compare performance of each cell and identification of faulty cell operation for activation, ohmic and mass transfer losses regions. The biggest difference in impedance value between healthy and faulty cell was registered for mass transfer losses region. The authors discussed the statistical selection of an equivalent circuit based on the course of χ 2 value in the function of current. Highlights: Dynamic impedance measurements simultaneously on stack and single cell level. New diagnostics method of PEM fuel cells in real operating conditions. Detection of malfunction cell with fault characterization. The best statistical equivalent circuit for whole range of operations.